PENGEMBANGAN BAHAN AJAR BERBASIS ADOBE FLASH PADA PEMBELAJARAN AKUNTANSI PERUSAHAAN DAGANG UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SMK NEGERI 1 SURAKARTA - -, Ernawati; -, Siswandari; -, Sohidin (FKIP Universitas Sebelas Maret, 2016)
ABSTRACTThe objective of this research is to investigate the feasibility and effectiveness of Adobe Flash-base learning material in Trading Company Accounting to improve the learning achievement of the students of State Vocational High School 1 of Surakarta. This research used the research and development (R&D) method. It employed the procedure of R & D claimed Borg and Gall modified into eight phases, namely: (1) preliminarily research and data collection, (2) planning, (3) development of initial product format, (4) design validation, (5) initial experiment, (6) product revision, (7) field experiment, (8) final product revision. The learning material was validated by three experts, and then it was experimented to 30 students in Grade XI Accounting 2 of State Vocational High School 1 of Surakarta as the experimental class. The research also involved 32 students in Grade XI Accounting 1 of the school as the control class. The data of research during the development were analyzed by using qualitative model of analysis claimed Miles and Huberman; the feasibility of the developed learning material was analyzed by using the score of criteria; and the learning achievement was analyzed by using the t test. The results of research are as follows. Firstly, the developed Adobe Flash-based learning material belongs to the very good category if viewed from the aspects of content feasibility, language, presentation, and graph. Secondly, the developed Adobe Flash-based learning material is effective to improve the learning achievement of the students of State Vocational High School 1 of Surakarta as indicated by the result of the t test = 0.000 which was smaller than 0.05, meaning that there was a significant difference in the average score between the experimental class and the control class. The experimental class has a higher average score improvement than the control class; the average score of the former increased as many as 31.6 points from 59.07 to 90.67, whereas the that of the latter increased as many as 13.66 points from 60.28 to 73.94.Keywords: learning material, Adobe Flash, Adobe Flash-based learning material, learning achievement ABSTRAKPenelitian ini bertujuan untuk mengetahui kelayakan dan keefektifan bahan ajar berbasis Adobe Flash pada pembelajaran Akuntansi Perusahaan Dagang dalam meningkatkan prestasi belajar siswa XI Akuntansi SMK Negeri 1 Surakarta. Penelitian ini merupakan penelitian pengembangan atau Research and Development (R&D). Penelitian pengembangan bahan ajar berbasis Adobe Flash ini menggunakan prosedur Borg dan Gall yang dimodifikasi menjadi delapan langkah yaitu: 1) penelitian dan pengumpulan informasi awal, 2) perencanaan, 3) pengembangan format produk awal, 4) validasi desain, 5) uji coba awal, 6) revisi produk, 7) uji coba lapangan, dan 8) revisi produk akhir. Bahan ajar divalidasi oleh tiga ahli, selanjutnya diujicobakan kepada 30 siswa kelas XI Akuntansi 2 SMK Negeri 1 Surakarta sebagai kelas eksperimen dengan melibatkan 32 siswa kelas XI Akuntansi 1 SMK Negeri 1 Surakarta sebagai kelas kontrol. Analisis data yang digunakan selama pengembangan adalah analisis kualitatif dengan model Miles dan Huberman, analisis kelayakan bahan ajar berdasarkan skor kriteria, dan analisis prestasi belajar melalui t-test. Hasil penelitian sebagai berikut. Pertama, bahan ajar berbasis Adobe Flash termasuk dalam kategori sangat baik ditinjau dari aspek kelayakan isi, kebahasaan, sajian, dan kegrafikaan. Kedua, bahan ajar berbasis Adobe Flash pada pembelajaran Akuntansi Perusahaan Dagang efektif meningkatkan prestasi belajar siswa SMK Negeri 1 Surakarta. Analisis independent sample t-test menunjukkan perolehan signifikansi 0,000 atau kurang dari 0,05 memiliki makna terdapat perbedaan nilai rata-rata antara kelas eksperimen dan kontrol secara signifikan. Peningkatan nilai rata-rata kelas eksperimen lebih tinggi daripada kelas kontrol. Nilai rata-rata kelas eksperimen meningkat 31,6 point dari 59,07 menjadi 90,67, sedangkan nilai rata-rata kelas kontrol hanya meningkat 13,66 point dari 60,28 menjadi 73,94.Kata Kunci : bahan ajar, Adobe Flash, bahan ajar berbasis Adobe Flash, prestasi belajar